2018
DOI: 10.1038/s41598-018-26350-3
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Cone Photoreceptor Localisation in Healthy and Stargardt Afflicted Retinas Using Deep Learning

Abstract: We present a robust deep learning framework for the automatic localisation of cone photoreceptor cells in Adaptive Optics Scanning Light Ophthalmoscope (AOSLO) split-detection images. Monitoring cone photoreceptors with AOSLO imaging grants an excellent view into retinal structure and health, provides new perspectives into well known pathologies, and allows clinicians to monitor the effectiveness of experimental treatments. The MultiDimensional Recurrent Neural Network (MDRNN) approach developed in this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…Nevertheless, the smaller size of cones and higher density near the fovea meant that a similar number of cones could still be selected for the normal database even with a higher exclusion rate. While we do not expect that exclusion of cones with weak boundaries will affect the accuracy of the normal database, in the future, further enhancement of segmentation accuracy of crowded cones could be achieved by training the cone boundary classifier through deep learning 54 , 55 and applying the classifier to separate touching cells. 56 Fourth, in addition to cone diameter, second-order metrics based on cone segmentation might lead to additional insights about diseases such as Best disease, in which cones have been reported to be noncircular.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the smaller size of cones and higher density near the fovea meant that a similar number of cones could still be selected for the normal database even with a higher exclusion rate. While we do not expect that exclusion of cones with weak boundaries will affect the accuracy of the normal database, in the future, further enhancement of segmentation accuracy of crowded cones could be achieved by training the cone boundary classifier through deep learning 54 , 55 and applying the classifier to separate touching cells. 56 Fourth, in addition to cone diameter, second-order metrics based on cone segmentation might lead to additional insights about diseases such as Best disease, in which cones have been reported to be noncircular.…”
Section: Discussionmentioning
confidence: 99%
“…CNNs have shown promise for automatically identifying cones in AOSLO images of normal retina 27 and images from patients with achromatopsia 28 and Stargardts. 29 In the present study, we used the open source split-detection CNN developed by Cunefare et al 27 and showed that the Dice coefficient for the CHM-trained split-detection CNN selections in comparison to manual selections ranged from 0.78 to 0.85 for different graders (see Table 4). This is comparable to results using the same split-detection CNN retrained for achromatopsia (Dice coefficient, 0.867) 28 and for Stargardt's (Dice coefficient, 0.8797).…”
Section: Discussionmentioning
confidence: 87%
“…28 In addition, a multidimensional recurrent neural network has been shown to yield automatic cone identifications in Stargardt disease in good agreement with manual identifications. 29 However, it remains to be determined to what extent these techniques can be applied to patients with other retinal diseases as different diseases present with varying phenotypes in AOSLO images. 2 In the present study, we address the issues described above for translating quantifications of cone metrics for CHM into ones that can be readily applied to longitudinal clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an opportunity to apply machine learning to address this clinical need. Currently, the only application of machine learning to Stargardt disease image analysis is limited to cone detection in adaptive optics scanning light ophthalmoscope split-detection images, as described by Davidson et al 40 …”
Section: Introductionmentioning
confidence: 99%